Effects of three major protein sources on performance, gut morphology and fermentation characteristics in broilers. Issue 1 (2nd January 2020) - Qaisrani, S. N.; Van Krimpen, M. M.; Verstegen, M. W. A.; Hendriks, W. H.; Kwakkel, R. P.
ABSTRACT: 1. This study determined the effects of three protein sources (PS), each at two digestibility crude protein (DCP) levels, on performance, gut morphology and fermentation characteristics in the hindgut of broilers. 2. It was hypothesised that broilers fed ingredients high in indigestible CP, i.e. rapeseed meal (RSM) or maize gluten (MG), could potentially cause reduced growth, impaired gut health, and more protein fermentation products in caecal digesta. Increasing the DCP level in each of the indigestible CP diets may compensate for these detrimental effects. 3. In total, 288 one-d-old male Ross 308 broilers were used in a completely randomised 3 × 2 factorial design, with six replicate pens per treatment. Three PS: soybean meal (SBM), rapeseed meal (RSM) or maize gluten (MG), and two DCP levels: 15.8 and 17.2% were used. 4. Broilers fed SBM had increased feed intake and BWG and improved FCR compared with those fed RSM and MG diets. Broilers fed high DCP had better performance compared with those on low DCP. No significant effects of PS or DCP level were found on gastrointestinal tract development, caecal ammonia or volatile fatty acid concentrations. 5. Broilers fed SBM had longer villi, smaller crypts and increased villus height to crypt depth ratio compared with those fed RSM and MG diets. Broilers fed RSM diet had a lower caecal pH, and had 16.5% and 14.9% more branched chain fatty acid contents in caecal digesta compared with those fed SBM and MG diets, respectively, indicating more proteolytic fermentation. 6. Replacing SBM by RSM and MG negatively affected growth performance and gut morphology. Hindgut protein fermentation was substantially increased in RSM fed birds. 7. To a certain extent, retarded growth performance in RSM and MG fed birds could be counterbalanced by increasing the dietary level of digestible CP.